2018
DOI: 10.2478/v10038-012-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to concomitant low health-related physical fitness components and associated sociodemographic factors in Brazilian adolescents

Abstract: Purpose. To determine the prevalence of the presence of concomitant low health-related physical fitness components with sociodemographic factors among Brazilian adolescents living in a small town of German colonization. Methods. A cross-sectional epidemiological study on adolescents (10 to 17 years old) from the public schools of São Bonifácio, Santa Catarina, Brazil (N = 277) was conducted. The FITNESSGRAM test battery was applied to assess three physical fitness components (body com position, cardiorespirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…These results corroborate findings in literature, which verified high prevalence of students with negative physical fitness indicators 3,9 . A survey conducted in a city in southern Brazil with students of the same age group as the present study found that 75.4% of boys and 88.5% of girls presented low physical fitness in at least one physical fitness indicator (body composition, muscle and cardiorespiratory fitness).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These results corroborate findings in literature, which verified high prevalence of students with negative physical fitness indicators 3,9 . A survey conducted in a city in southern Brazil with students of the same age group as the present study found that 75.4% of boys and 88.5% of girls presented low physical fitness in at least one physical fitness indicator (body composition, muscle and cardiorespiratory fitness).…”
Section: Discussionsupporting
confidence: 82%
“…The results identified in the present study in relation to the high prevalence of students who individually and simultaneously presented negative physical fitness indicators should be observed with caution, since the large number of cutoff points used to classify physical fitness indicators indicate a lack of consensus on the standardization to be used 1,2,6,9 . Thus, further studies should be carried out to determine specific cutoff points based on reference parameters in order to allow the comparison of results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health related physical fitness has been focused on body composition which has connected with morphological, functional and motor skills, cardiovascular and muscular (flexibility, power and strength) fitness (Minatto et al, 2012). Cardiovascular fitness has been a result of physical activity and an important component of metabolic health (Mota et al, 2012).…”
Section: Introductionmentioning
confidence: 99%